The Application of Some Linear Feedback Control Strategies on 3D Chaotic System - Mahasin Younis (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper tackles to some linear feedback control strategies, where we take a 3D chaotic system with a five critical point of unstability, which is discovered by scientist [Zhu Congxu, 2010]. So we applied some linear feedback strategies: first strategy Ordinary Feedback Control and the second strategy Dislocate Feedback Control on this system at origin point and we noticed that a necessary condition for suppression is getting positive feedback coefficient; but this condition fails at some strategies. For this reason, we focused on these cases in our search, and design more than a strategy for studying these different situations. Theoretical analysis and numerical simulation check the validity of the results obtained.